Proceedings of the 55th Annual Meeting of the Association For Computational Linguistics (Volume 1: Long Papers) 2017
DOI: 10.18653/v1/p17-1065
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-to-Dependency Neural Machine Translation

Abstract: Nowadays a typical Neural Machine Translation (NMT) model generates translations from left to right as a linear sequence, during which latent syntactic structures of the target sentences are not explicitly concerned. Inspired by the success of using syntactic knowledge of target language for improving statistical machine translation, in this paper we propose a novel Sequence-to-Dependency Neural Machine Translation (SD-NMT) method, in which the target word sequence and its corresponding dependency structure ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(61 citation statements)
references
References 18 publications
(24 reference statements)
1
59
0
1
Order By: Relevance
“…In this work, we model syntactic information of target tokens using an additional sequence of variables, which captures the syntactic choices 1 at (a) Full co-dependence model. (Wang et al, 2018a;Wu et al, 2017;Aharoni and Goldberg, 2017). (c) LaSyn, our latent syntax model that uses non-sequential latent variables for exhaustive search of latent states.…”
Section: A Latent Syntax Model For Decodingmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we model syntactic information of target tokens using an additional sequence of variables, which captures the syntactic choices 1 at (a) Full co-dependence model. (Wang et al, 2018a;Wu et al, 2017;Aharoni and Goldberg, 2017). (c) LaSyn, our latent syntax model that uses non-sequential latent variables for exhaustive search of latent states.…”
Section: A Latent Syntax Model For Decodingmentioning
confidence: 99%
“…Aharoni et al (2017) treated constituency trees as sequential strings and trained a Seq2Seq model to translate source sentences into these tree sequences. Wang et al (2018a) and Wu et al (2017) proposed to use two RNNs, a Rule RNN and a Word RNN, to generate a target sentence and its corresponding tree structure. Gu et al (2018) proposed a model to translate and parse at the same time.…”
Section: Model Bleumentioning
confidence: 99%
“…Recent efforts have demonstrated that incorporating linguistic information can be useful in NMT [7,12,15,17,22,23]. Since the source sentence is definitive and easy to attach extra information, it is a straightforward way to improve the translation performance by using the source side features [12,17].…”
Section: Related Workmentioning
confidence: 99%
“…Unlike prior work on syntactic decoders designed for utilizing a specific type of syntactic information (Wu et al, 2017), TrDec is a flexible NMT model that can utilize any tree structure. Here we consider two categories of tree structures:…”
Section: Tree Structuresmentioning
confidence: 99%